EXAMINATION OF SETS OF POINTS AND NON-NULL LINES UNDER THE TWO-PARAMETER LORENTZIAN MOTION - Senturk, Gulsum Yeliz; Yuce, Salim (EDITURA BIBLIOTHECA-BIBLIOTHECA PUBL HOUSE, 2020)
In this paper, firstly, we interested in finding the relationships among the densities of sets of collinear points, among the densities of non-collinear points and among the densities of sets of intersecting non-null lines in Lorentzian plane. Furthermore, we concerned with the density formulas of sets of points and the sets of non-null lines under the two-parameter planar Lorentzian motion.
Keywords: point density; line density; two-parameter motion; Lorentzian plane; Science & Technology - Other Topics